The Influence of Reward, Work Motivation on Nurse Performance in Inpatient Rooms - Sultan; Yuly Peristiowati (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Nurse performance is determined by many factors, among which the most important is reward and motivation given to nurses. The implementation of a clear system will have a positive impact on the performance of nurses in providing health services. The purpose of this study was to determine the effect of reward and motivation on the performance of nurses in inpatient rooms at hospitals. The research method used is Systematic Literature Review which is based on online data on Google Scholar, Scopus, Pubmed. Articles were searched from January – March 2023. Seven articles from the majority database stated that there was an effect of reward and motivation on nurse performance.